Influence of tool rotational speed on the evolution of microstructure and mechanical properties of precipitation-hardened Aluminium 6061 butt joint during friction stir welding. (21st January 2022) - Ghosh, Biplab; Das, Hrishikesh; Samanta, Asis; Majumdar, Jyotsna Dutta; Ghosh, Manojit
Abstract: The present investigation aims to evaluate the influence of varying tool rotational speed (rotation per minute, rpm) on the mechanical properties and microstructural evolution within friction stir welded aluminium alloyAA6061-T6 joints. The effects of rpm underthe constant tool travel speedwere investigated by optical microscopy, field emission scanning electron microscopy (FESEM)and transmission electron microscopy (TEM)observation, tensile, fracture and micro-hardness test. Special attention was paid to the formation and evolution ofprecipitates.Results revealed that the tool rotational speedof 1300 rpmproduces highest hardness reaching to ∼69 HVN at the nugget zone (NZ), which could be attributed to the higher intensity of nano-sized re-precipitation. This specific tool rotational speed of 1300 rpm has been determined to be suitable to achieve the maximum joint efficiency of 70.6%. Significantly, the NZ is characterized with small equiaxed dynamically recrystallized grains. In a noteworthy findings, the NZ showed mostly either free from strengthening precipitate or trace of small tiny re-precipitates, while the thermo-mechanically affected zone (TMAZ) contains coarse precipitates with deformed and dynamically recovered grains. On the other hand, there was obvious grain growth with increasing rpm, substantiating more heat involvement with favourable thermal gradient. The experiment concludes thatthe rotational speed has an considerable effect on the precipitation characteristics, dislocation property and existence of finer second phase intermetallic compounds (IMC), which arethe predominant factors controlling the joint property.